Climate change impacts on shoreline migration and community livelihood resilience: evidence from coastal Bangladesh - Islam, Md. Tariqul; Hossain, Md. Monabbir; Ha-Mim, Nur Mohammad; Hossain, Md. Zakir; Sikder, Sujit Kumar (Frontiers in Sustainability, 2025)
The livelihoods of coastal people are at risk as shoreline migration is accelerated by climate change. To safeguard these communities and maintain their economy, it is imperative to strengthen resilience via adaptive strategies. Therefore, this study aims to estimate the rates and impacts of physical shoreline migration over the past 9,000 years using geospatial analysis and focus on understanding the livelihood resilience of coastal at-risk communities using in-depth interviews with environmental experts. The dynamic system of the Ganga-Brahmaputra-Meghna is highly complex and causes continuous shoreline migration. Historical data and more recent satellite remote sensing imagery analysis identified that the shrinking of the delta system has resulted from the migration of the shorelines at the mouth of the river system. Since 5,000 BP, it has been expanding towards the Bay of Bengal – meaning land gains at the coast. Land gain provides an opportunity for the extension of coastal communities but also increases their vulnerability to natural hazards. Moreover, by 2050, the salinity isoline with a 5-ppt is expected to shift inland by ⁓8 km in the south-east (Bhola-Patuakhali) and ⁓24 km in the southwest (Khulna-Satkhira) region. The in-depth interviews reveal several adaptive practices to effectively deal with the situation, including community knowledge, stakeholder engagement, local-led adaptation, and most importantly, temporal migration. The findings also highlighted the urgent need for an adaptation plan for the sustainability and resilience of coastal communities, considering indigenous knowledge with local cultural orientation and incorporation of scientific standards.